Correction to: Improved Dust Detection over East Asia Using Geostationary Satellite Data - Yu-Rim Shin; Eun-Ha Sohn; Ki-Hong Park; Geun-Hyeok Ryu; Soobong Lee; Seon-yong Lee; Na-Yeon Park (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Improved Dust Detection over East Asia Using Geostationary Satellite Data - Yu-Rim Shin; Eun-Ha Sohn; Ki-Hong Park; Geun-Hyeok Ryu; Soobong Lee; Seon-Young Lee; Na-Yeon Park (Asia-Pacific Journal of Atmospheric Sciences, 2021)
This paper presents an improved algorithm, based on the D*-parameter, for dust detection over the East Asian region using brightness temperature differences (BTDs) between the infrared channels of the Advanced Himawari Imager (AHI) onboard Himawari-8. The developed algorithm defines a dust index in the form of the ratio of BTDs: BTD between the 10.4 μm and 12.4 μm channels (BTD 10.4–12.4 ) to that between the 8.6 μm and 10.4 μm channels (BTD 8.6–10.4 ). To identify dust with this index, threshold values were determined empirically. A masking technique using the BTD 8.6–10.4 was utilized in the dust index to mitigate the problem of detecting clear-sky deserts and fog over the ocean as dust. BTD 8.6–10.4 was analyzed for dust, clear-sky desert, and fog over the ocean cases during 2017 and 2018 with this method. Fog over the ocean and clear-sky desert were distinguished by the criteria of BTD 8.6–10.4 > −1.1 K and BTD 8.6–10.4 > −1 K, respectively. Based on these thresholds, the influence of fog over the ocean and clear-sky desert was filtered out. The results showed that the dust area was qualitatively consistent with RGB images and ground observation data. Comparison with the AERONET aerosol optical depth (AOD) demonstrated that the D*-parameter was exponentially proportional to AOD, and the correlation coefficient between them was approximately 0.6. The improved Asian Dust detection algorithm can be applied to the monitoring of dust dispersion and movement and also serve as a quantitative indicator of Asian Dust.